Characterization and Chemical Treatment of Taman Beringin Landfill Leachate - M, Nor Asikir; P, Agamuthu (Malaysian Journal of Science, 2007)
Characterization of landfill leachate from Taman Beringin landfill, Kuala Lumpur, Malaysia was carried out immediately after sample collection. Subsequently, it was treated using alum, ferric chloride (FeClÃ¢â€šÆ’), Fenton’s reagent and polyaluminium chloride (PAC) individually. Raw leachate contained COD (5400 mg/L), BOD (1900 mg/L), NHÃ¢â€šÆ’-N (3500 mg/L), sulphide (68 mg/L), chloride (260 mg/L) and heavy metals such as Pb (3.38 mg/L), Cu (0048 mg/L), Zn (4.5 mg/L) and Fe (35.8 mg/L). All these parameters were above the EQA 1974 (Standard A and B) limit. At optimal ratio of 1:6 (Fe to HÃ¢â€šâ€šOÃ¢â€šâ€š), with rapid and slow mixing at 100 - 120 rpm and 30 - 40 rpm, respectively Fenton’s reagent was able to reduce about 62% of COD, 58% of BOD, 65% of NHÃ¢â€šÆ’-N, 100% of Pb, Cu and Zn, 95% of Al and 82% of Fe. PAC, also at optimal concentration of 0.4g/500 ml, and at pH of 7 with rapid and slow mixing at 100 - 120 rpm and 30 - 40 rpm, was capable of reducing COD and BOD by 59% and 55% respectively. The reduction of NHÃ¢â€šÆ’-N, Pb, Al, Fe, Cu and Zn ranged from 51% to 100%. At the optimum concentration of 5g/500ml, alum was capable of reducing about 53% of COD, 49% of BOD, 63% of NHÃ¢â€šÆ’-N, 99% of Pb, 100% of Cu, 91% of Al, 100% of Zn and 81% of Fe. Finally, FeClÃ¢â€šÆ’, at optimum concentration, pH and mixing speed, reduced COD by 38% while BOD was reduced by 42%. The reduction of NHÃ¢â€šÆ’-N, Pb, Al, Zn and Fe ranged from 41 % to 85%. Fenton’s reagent was most effective in reducing most of the above parameters compared to PAC, alum and FeClÃ¢â€šÆ’. Some parameters such as COD, BOD, NHÃ¢â€šÆ’-N, Al and Fe still exceeded the EQA 1974 (Standard A and B), although Fenton’s reagent was able to reduce Pb, Cu and Zn to below the EQA Standard. Affiliation: